Mechanistic analysis of Tanshinone IIA’s regulation of the ATM/GADD45/ORC signaling pathway to reduce myocardial ischemia-reperfusion injury - Sang, Yiwei; Du, Jiangnan; Zulikala, Dilimulati; Sang, Zhongqiang (Frontiers in Pharmacology, 2024)
BackgroundBy far, one of the best treatments for myocardial ischemia is reperfusion therapy. The primary liposoluble component of Danshen, a traditional Chinese herbal remedy, Tanshinone ⅡA, has been shown to have cardiac healing properties. The purpose of this work is to investigate the processes by which Tanshinone ⅡA influences myocardial ischemia-reperfusion injury (MIRI) in the H9C2 cardiac myoblast cell line, as well as the association between Tanshinone ⅡA and MIRI.Methods and resultsThe cardiac cells were divided into a normal group, a model group and Tanshinone ⅡA treatment groups. After 4 h of culture with the deprivation of oxygen and glucose, the cells were incubated normally for 2 h. The success of the model and the capacity of Tanshinone ⅡA to heal cardiac damage were validated by the outcomes of cell viability, morphology, and proliferation. The efficacy of Tanshinone ⅡA in treating MIRI was further confirmed by the scratch assay and biomarker measurement. The differentially expressed genes were examined using transcriptome sequencing. The Ataxia-Telangiectasia Mutated (ATM)/Growth Arrest and DNA Damage (GADD45)/Origin Recognition Complex (ORC) signaling pathway was identified as being crucial to this process by KEGG pathway analysis and GO enrichment. Molecular docking and RT-qPCR were used to confirm our results. The crucial function of the ATM/GADD45/ORC pathway was further confirmed by the addition of an ATM inhibitor, which inhibited the expression of ATM.ConclusionTanshinone ⅡA can relieve the myocardial ischemia-reperfusion injury in cardiac cells by activating the ATM/GADD45/ORC pathway.